2012
DOI: 10.1007/s00018-012-0936-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of latent HIV-1 by a wide variety of butyric acid-producing bacteria

Abstract: Latently infected cells harbor human immunodeficiency virus type 1 (HIV-1) proviral DNA copies integrated in heterochromatin, allowing persistence of transcriptionally silent proviruses. It is widely accepted that hypoacetylation of histone proteins by histone deacetylases (HDACs) is involved in maintaining the HIV-1 latency by repressing viral transcription. HIV-1 replication can be induced from latently infected cells by environmental factors, such as inflammation and co-infection with other microbes. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 50 publications
2
75
1
1
Order By: Relevance
“…In contrast to previous studies, which focused on the effect of butyrate on reactivation of HIV-1 in latently infected cells (6), the present results underscore the impact of acetate exposure on the permissiveness of primary human CD4 ϩ T cells to productive HIV-1 infection. Our observations revealed that acetate enhances the susceptibility of primary human CD4 ϩ T cells to productive HIV-1 infection (i.e., a greater proportion of HIV-1-infected cells) without affecting virus gene expression at the single-cell level ( Fig.…”
Section: Figcontrasting
confidence: 86%
See 1 more Smart Citation
“…In contrast to previous studies, which focused on the effect of butyrate on reactivation of HIV-1 in latently infected cells (6), the present results underscore the impact of acetate exposure on the permissiveness of primary human CD4 ϩ T cells to productive HIV-1 infection. Our observations revealed that acetate enhances the susceptibility of primary human CD4 ϩ T cells to productive HIV-1 infection (i.e., a greater proportion of HIV-1-infected cells) without affecting virus gene expression at the single-cell level ( Fig.…”
Section: Figcontrasting
confidence: 86%
“…Resulting from the fermentation of indigestible food components by anaerobic commensal bacteria composing the gut microbiome (8-10, 14, 17, 19-24), SCFAs have been suggested to affect HIV-1-mediated disease progression (1)(2)(3)(4)(5)(6)(7)42). Previous studies have focused on the impact of the SCFA butyrate on reactivation of the provirus in cells latently infected with HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…The progression to AIDS is influenced by host inflammatory responses and coinfection with other pathogens such as viruses, fungi, parasites, and bacteria (3,20,(42)(43)(44)(45). In particular, opportunistic infection frequently sets in when an HIV-infected individual is immunocompromised.…”
Section: Hiv Latency As a Critical Obstacle To The Eradication Of Hivmentioning
confidence: 99%
“…We found that among the various virulence factors produced by this Gram-negative anaerobe, a high concentration of butyric acid in the culture supernatant and the augmenting effect of HIV replication were abolished upon its removal. To confirm these observations, we attempted to comprehensively examine the human resident butyric acid-producing bacteria from various tissues (20). We found that bacterial culture supernatants of P. gingivalis, Fusobacterium nucleatum, Clostridium cochlearium, and Anaerococcus tetradius increased histone acetylation and efficiently induced HIV gene expression from the latent state.…”
mentioning
confidence: 98%
See 1 more Smart Citation